Determining Production Scale of Lele Dumbo at Central of Lampung Regency - Fitriani Fitriani; Sutarni Sutarni (Jurnal Ilmiah ESAI, 2011)
Determining production scale is important role in farming.  Lele dumbo growth cultivation contributed on enlargement of family income in rural. The goal of the research was to determine the production scale of lele dumbo growth.   The research did on April until November 2006 located at Central Lampung Regency, Lampung Province. The location determined purposively considering that lele dumbo production was higher than others. The survey method was done by survey.  Forty farmers were choosen as respondents purposively.  The model of research was built on Frontier production function.  The result of research performed that the lele dumbo growth on the decreasing returns to scale or at the rational stage (stage II).  Key words:  production scale, frontier production function, lele dumbo growth